2005
DOI: 10.1111/j.1471-4159.2004.02959.x
|View full text |Cite
|
Sign up to set email alerts
|

Inherited and acquired interactions between ACHE and PON1 polymorphisms modulate plasma acetylcholinesterase and paraoxonase activities

Abstract: The 5.5 Mb chromosome 7q21-22 ACHE/PON1 locus harbours the ACHE gene encoding the acetylcholine hydrolyzing, organophosphate (OP)-inhibitable acetylcholinesterase protein and the paraoxonase gene PON1, yielding the OP-hydrolyzing PON1 enzyme which also displays arylesterase activity. In search of inherited and acquired ACHE-PON1 interactions we genotyped seven polymorphic sites and determined the hydrolytic activities of the corresponding plasma enzymes and of the AChE-homologous butyrylcholinesetrase (BChE) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 52 publications
2
46
1
Order By: Relevance
“…The carriers of R allele were found to be better responders [27]. This influence of the polymorphism could result from the interaction between PON1 and cholinesterase [4,21].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The carriers of R allele were found to be better responders [27]. This influence of the polymorphism could result from the interaction between PON1 and cholinesterase [4,21].…”
Section: Introductionmentioning
confidence: 95%
“…Several authors reported that when PON1 activity was measured using arylester as a substrate, no differences depending on Q192R polymorphism were observed. It was often admitted that paraoxon was a discriminating substrate and phenylacetate was a non-discriminating one [4,9,20,23].…”
Section: Introductionmentioning
confidence: 99%
“…To compare the effects of AChE, BChE and cholinergic status changes on cardiovascular risk, we used ATCh as a substrate with or without tetraisopropyl pyrophosphoramide (iso-OMPA, a specific BChE inhibitor), thus identifying AChE alone, mimicking the total impact of ACh hydrolysis and enabling a calculation of BChE contribution. This method has been reliably used in several recent studies (14,(19)(20)(21)(22)(23).…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Interestingly, the genes which code for PON-1 and AchE, the major target for OP compounds, are located in close proximity on chromosome 7q21-22. This suggests that polymorphisms in these adjacent genes can impact each other's expression, which can impact sensitivity to agents that inhibit cholinesterase enzymes [11].…”
Section: Op Compound Metabolism and Toxicitymentioning
confidence: 99%
“…This evidence also suggests that not only is PON-1 protective against OP toxicity, but that exogenous PON-1 may have a potential therapeutic role in protecting individuals exposed to OP compounds (agricultural workers exposed to pesticides or soldiers at risk for exposure to a nerve agent). Thus far, only one study exists which incorporated objective data into its methodology, (cholinesterase testing results), which were determined to be poor markers for OP toxicity [11]. In addition to PON-1 genotype, direct measurement of PON-1 activity and correlation with signs, symptoms, and objective data in real patients may also help to increase understanding of the importance of PON-1 in OP metabolism and toxicity.…”
Section: Op Compound Metabolism and Toxicitymentioning
confidence: 99%